Illuminating the dark: PEGylated carboxylated graphene quantum dots and curcumin in nucleolar activity and PDT-induced DNA damage in cancer - Dilenko, Hanna; Bartoň Tománková, Kateřina; Hinde, Elizabeth; Válková, Lucie; Kolaříková, Markéta; Kolářová, Hana (Biomedicine & pharmacotherapy, 2025)
Many photosensitive substances suitable for photodynamic therapy (PDT) have limited applications due to their insufficient solubility in polar solvents. Our research overcomes this challenge by means of nanotechnology in order to transform hydrophobic compounds into stable aqueous solutions, enabling them to use their full potential and unique properties in cancer therapy. In this study, the novel nano-composite cGQDs-PEG-curcumin was developed to overcome the insolubility of curcumin in water and its extraordinary efficacy in PDT was evaluated. Complex characterization was performed using high-resolution transmission electron microscopy (HR-TEM), FTIR, and UV-Vis spectroscopy. Further analysis involved fluorescence lifetime imaging (FLIM), and its cellular localization was mapped with confocal microscopy. In order to evaluate PDT effectiveness, cells treated with cGQDs-PEG-curcumin were irradiated with 5 J/cm2 of 414 nm light. After irradiation, cell viability assay, scanning electron microscopy (SEM), reactive oxygen species (ROS) detection, comet assay, and γH2AX-based DNA double-strand breaks (DSBs) detection were assessed and revealed a remarkable ability of the nano-composite to induce DNA damage after irradiation without ROS production. Our findings highlight the potential of cGQDs-PEG-curcumin as a cutting-edge PDT agent, capable of disrupting cell membrane and nucleolar integrity and impairing ribosomal synthesis, which is crucial for proliferating tumour cells.
Keywords: Photochemotherapy; poškození DNA; viabilita buněk; polyethylenglykoly; fotosenzibilizující látky; Neoplasms; fotochemoterapie; DNA Damage; Cell Line, Tumor; Photosensitizing Agents; reaktivní formy kyslíku; Cell Nucleolus; kurkumin; grafit; Cell Survival; kvantové tečky; dvouřetězcové zlomy DNA; DNA Breaks, Double-Stranded; Quantum Dots; Graphite; Reactive Oxygen Species; Nanomedicine; Polyethylene Glycols; lidé; Humans; Drug delivery; Curcumin; nádory; DNA double-strand breaks; nádorové buněčné linie; buněčné jadérko; Photosensitizers